SUMATERA UTARA: PENGEMBANGAN POTENSI DAERAH DALAM DIKOTOMI SPASIAL DAN NON SPASIAL - Ginting, Erika Sari (Universitas Medan Area, 2020)
North Sumatera is a province with various characteristics, both spatial and non -spatial. For many years there has been a debate about the large spatial gaps in development exist in North Sumatera. In this paper, the province is divided into four groups. The allocation of a regency into a group based on two dichotomies. Firstly, the spatial dichotomy between the regencies near Lake Toba and outside the lake area. Secondly, the economic development dichotomy among the regions of North Sumatera. The method to determine high or low growth region was Typology Klassen. The result is two region near the Lake Toba are high growth regions, however five of them are still stated as low growth regions. Meanwhile, for the regions outside Lake Toba, six of them are high growth regions and eight of them are still in the low growth regions. In order to improve the economic growth of every region, it is important to promote and develop strategic local.